Resistance in Rice Breeding Lines to the Blast Fungus in Nepal (Nepal Agriculture Research Journal, 2010)
A total of 36 rice breeding lines including checks were evaluated for resistance to blast atRampur during 2000-2001. The experiments were conducted under both field condition andgreenhouse inoculated condition. Qualitative resistance in rice to blast was assessed based onlesion type, whereas quantitative resistance was assessed based on area under disease progresscurve (AUDPC) in the upland field condition. The number of sporulating lesions and the numberof leaves with at least one sporulating lesion per plant were considered as measures forevaluation of quantitative resistance in the greenhouse assay. The lesion type, neck blastpercentage and AUDPC data suggest that most of the rice lines possess higher level of resistanceto leaf and neck blast. The rice lines varied for the number of sporulating lesions and the numberof leaves with sporulating lesion per plant. Some lines were incompatible to virulent blastisolates, showing major resistance genes. NR 1558, NR 601-1-1-9, BW306-2 and CN 836-3-10were promising lines for quantitative resistance to both leaf and neck blast. Radha 12, Sabitri,Janaki possess higher level of quantitative resistance to blast, hence these could be promoted forcultivation in blast-prone environments. These genotypes could also be utilized as donor parentsfor breeding durable blast resistant varieties. The most virulent blast isolate could be used forevaluation of both qualitative and quantitative resistance to blast in early generation in thegreenhouse so that workload could be cut down in future works.Key words: Blast resistance; field condition; greenhouse assay; Pyricularia grisea; rice linesDOI: 10.3126/narj.v6i0.3344Nepal Agriculture Research Journal Vol.6 2005 pp.49-56